Sex-specific lung diseases: effect of oestrogen on cultured cells and in animal models - Shim, Bosung (Eur Respir Rev, 2013)
Sex prevalence in lung disease suggests that sex-specific hormones may contribute to the pathogenesis and/or progression of at least some lung diseases, such as lung adenocarcinoma, lymphangioleiomyomatosis (LAM) and benign metastasising leiomyoma (BML). Oestrogen is an important hormone in normal lung development and in the pathogenesis of female predominant pulmonary diseases. In vivo and in vitro studies have facilitated our understanding of disease pathogenesis and discovery of potential therapeutic targets. Oestrogen promoted disease progression in cell and animal models of lung adenocarcinoma, LAM and BML. Specifically, oestrogen enhanced tumour growth and metastasis in animal models of these diseases. Furthermore, 17β-estradiol (E(2)), the most abundant form of oestrogen in humans, increased the size and proliferation of cultured cells of lung adenocarcinoma and LAM. Coupled with the known mechanisms of oestrogen metabolism and signalling, these model systems may provide insights into the diverse effects of oestrogen and other hormones on lung diseases. Anti-oestrogen treatments that target key events of oestrogen synthesis or signalling, such as aromatase activity, oestrogen receptors and signalling pathways, may offer additional opportunities for clinical trials.